If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 37 = x + 48 Reorder the terms: 37 = 48 + x Solving 37 = 48 + x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-1x' to each side of the equation. 37 + -1x = 48 + x + -1x Combine like terms: x + -1x = 0 37 + -1x = 48 + 0 37 + -1x = 48 Add '-37' to each side of the equation. 37 + -37 + -1x = 48 + -37 Combine like terms: 37 + -37 = 0 0 + -1x = 48 + -37 -1x = 48 + -37 Combine like terms: 48 + -37 = 11 -1x = 11 Divide each side by '-1'. x = -11 Simplifying x = -11
| 18m^2-77m-18=0 | | 3(0)=-y+3 | | 3-8h=35 | | 13-x=-8 | | 3(-2)=-y+3 | | 8x^2-46xy+11y^2=0 | | 30-3x=2+x | | 2m^2+13m+10=0 | | 2m^2-10-4=4 | | .5x+12=27 | | 16x-3y=18 | | 12x^2+133x+11=0 | | 350-167+v=2v | | 68+2x-30=x+42 | | Y+(-8)=-23 | | 24-x=42 | | 4x+5=2(3x+25) | | 6x-2=2x-10 | | (3x+8)(8x+7)=0 | | y=-0.50*40+121 | | y=-0.50*30+121 | | y=-0.50*20+121 | | 2x+48=322 | | 119=6x+17 | | 1500x=20x | | 1400+x=41900 | | 2x^2+4x-47=0 | | -16t^2+t+25=0 | | 2y^2+56=0 | | a+2b=-4 | | a+8b=8 | | 5x+1=-(x-7) |